Raw material for coating material for secondary battery separator, coating material for secondary battery separator, secondary battery separator, and secondary battery

By combining the reaction product of the modified hydroxymethyl melamine condensation resin with acidic groups and polyvinyl alcohol and inorganic particles, a secondary battery separator coating film with excellent heat resistance and ion permeability is formed, which solves the short circuit problem caused by the shape shrinkage of the separator under heat, and improves the overall performance of the separator.

CN119731861APending Publication Date: 2025-03-28MITSUI CHEMICALS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380060226.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-16
Filing Date
2023-11-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The secondary battery separator may shrink in shape under the action of heat, resulting in a short circuit between the positive electrode and the negative electrode, and the heat resistance and ion permeability of the existing coating materials are insufficient.

Method used

A coating material for a secondary battery separator containing a reaction product of a modified hydroxymethyl melamine condensation resin having an acidic group and a polyvinyl alcohol is used to form a coating film with excellent heat resistance and ion permeability by combining it with inorganic particles.

Benefits of technology

The heat resistance and ion permeability of the secondary battery separator are significantly improved, short circuit problems caused by heat shrinkage are avoided, and storage stability is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005274013230000041
    Figure BDA0005274013230000041
  • Figure BDA0005274013230000061
    Figure BDA0005274013230000061
  • Figure BDA0005274013230000221
    Figure BDA0005274013230000221
Patent Text Reader

Abstract

The raw material of the coating material for the secondary battery separator comprises a resin which is a reaction product of a modified hydroxymethyl melamine condensation resin having an acidic group and polyvinyl alcohol, or comprises a modified hydroxymethyl melamine condensation resin having an acidic group and polyvinyl alcohol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a raw material for a coating material for a secondary battery separator, a coating material for a secondary battery separator, a secondary battery separator, and a secondary battery. Specifically, it relates to a raw material for a coating material for a secondary battery separator, a coating material for a secondary battery separator containing the raw material for a coating material for a secondary battery separator, a secondary battery separator having a coating film of the coating material for a secondary battery separator, and a secondary battery having the secondary battery separator.

[0002] Conventionally, a secondary battery is provided with a separator for isolating a positive electrode from a negative electrode and allowing ions in an electrolyte solution to pass therethrough.

[0003] As such a separator, for example, a polyolefin porous film is known.

[0004] On the other hand, a coating layer may be provided on the surface of the separator in order to impart various physical properties. Such a coating layer is formed, for example, by applying a coating material for a secondary battery separator on the surface of the separator and drying it.

[0005] As such a coating material for a secondary battery separator, for example, a coating material for a secondary battery separator has been proposed, which comprises a coating material raw material for a secondary battery separator and an inorganic filler, wherein the coating material raw material for a secondary battery separator comprises a water-soluble polymer formed by polymerizing a water-soluble polymer raw material containing methacrylamide and methacrylic acid (for example, see Patent Document 1).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2021-103676 Summary of the invention

[0009] Problems to be solved by the invention

[0010] On the other hand, if the shape of the separator changes due to thermal shrinkage, a short circuit may occur between the positive electrode and the negative electrode. Therefore, heat resistance is required for the coating layer.

[0011] The present invention provides a raw material for a secondary battery separator coating having excellent heat resistance and ion permeability, a secondary battery separator coating material comprising the raw material for a secondary battery separator coating, a secondary battery separator having a coating film of the secondary battery separator coating material, and a secondary battery having the secondary battery separator.

[0012] Means for solving problems

[0013] The present invention [1] is a raw material for a secondary battery separator coating material, which comprises a resin which is a reaction product of a modified methylolmelamine condensation resin having an acidic group and polyvinyl alcohol, or comprises the aforementioned modified methylolmelamine condensation resin having an acidic group and the aforementioned polyvinyl alcohol.

[0014] The present invention [2] includes the secondary battery separator coating material raw material described in [1] above, which comprises the aforementioned resin, and the aforementioned acidic group is a sulfonic acid group.

[0015] The present invention [3] includes the raw material for coating material for secondary battery separator as described in the above [1], which comprises the aforementioned modified hydroxymethyl melamine condensation resin having an acidic group and the aforementioned polyvinyl alcohol, wherein the content ratio of the aforementioned polyvinyl alcohol is greater than 5 parts by mass and less than 50 parts by mass relative to 100 parts by mass of the aforementioned modified hydroxymethyl melamine condensation resin.

[0016] The present invention [4] includes a secondary battery separator coating material comprising the secondary battery separator coating material raw material according to any one of [1] to [3] above and inorganic particles.

[0017] The present invention [5] includes a secondary battery separator comprising: a porous membrane; and a coating film of the secondary battery separator coating material according to [4] above disposed on at least one surface of the porous membrane.

[0018] The present invention [6] includes a secondary battery comprising a positive electrode, a negative electrode, and the secondary battery separator described in [5] above disposed between the positive electrode and the negative electrode.

[0019] Effects of the Invention

[0020] The raw material of the secondary battery separator coating material of the present invention comprises a resin which is a reaction product of a modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol, or comprises a modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol, and therefore has excellent heat resistance and ion permeability.

[0021] The secondary battery separator coating material of the present invention contains the secondary battery separator coating material raw material of the present invention, and therefore has excellent heat resistance and ion permeability.

[0022] The secondary battery separator of the present invention includes a coating film of the secondary battery separator coating material of the present invention, and therefore has excellent heat resistance and ion permeability.

[0023] The secondary battery of the present invention includes the secondary battery separator of the present invention, and therefore has excellent heat resistance and ion permeability. DETAILED DESCRIPTION

[0024] The raw material for coating material for secondary battery separators includes a resin which is a reaction product of a modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol, or includes a modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol. Hereinafter, the first invention in which the raw material for coating material for secondary battery separators includes a resin which is a reaction product of a modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol, and the second invention in which the raw material for coating material for secondary battery separators includes a modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol are described in detail.

[0025] 1. Raw materials for coating materials for secondary battery separators

[0026] <<First Invention>>

[0027] The secondary battery separator coating material raw material contains a resin which is a reaction product of a modified methylolmelamine condensation resin having an acidic group and polyvinyl alcohol.

[0028] The resin is a reaction product of a modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol.

[0029] <Modified methylolmelamine condensation resin having an acidic group>

[0030] The modified methylolmelamine condensation resin having an acidic group (hereinafter, sometimes referred to as a modified methylolmelamine condensation resin) is a polycondensate of modified methylolmelamine.

[0031] The modified methylol melamine is a reaction product of methylol melamine and an acid component.

[0032] [Hydroxymethylmelamine]

[0033] Methylol melamine is a reaction product of melamine and formaldehyde or paraformaldehyde. When paraformaldehyde is used, the paraformaldehyde is hydrolyzed to formaldehyde and then reacted with melamine.

[0034] In order to react melamine with formaldehyde, water, melamine and formaldehyde are mixed and heated.

[0035] The amount of formaldehyde to be added per mol of melamine will be described in detail later, but from the viewpoint of increasing the molecular weight, it is, for example, 3.0 or more, preferably more than 3.0, more preferably 3.2 or more, further preferably 3.3 or more, and, for example, 5.0 or less, preferably 4.0 or less.

[0036] As heating conditions, the heating temperature is, for example, 40° C. or higher, preferably 50° C. or higher, and for example, 90° C. or lower, preferably 80° C. or lower. The heating time is, for example, 0.5 hour or higher, preferably 2 hours or higher, and for example, 6 hours or lower.

[0037] In the above reaction, the pH is 3.0 or more, preferably 4.0 or more, more preferably 8.0 or more, further preferably 9.0 or more, particularly preferably 10.0 or more, and for example, 13.0 or less, preferably 12.0 or less, more preferably 11.8 or less. The pH can be adjusted by adding a base (e.g., sodium hydroxide).

[0038] Thus, melamine (the following general formula (1-1)) and formaldehyde (the following general formula (1-2)) react to obtain methylolmelamine (the following general formula (1-3)).

[0039] [Chemical formula 1]

[0040] Chemical formula 1

[0041]

[0042] Preferably, methylolmelamine (the above general formula (1-3)) is trimethylolmelamine obtained by modifying 3 of 6 hydrogen atoms in the amino group of melamine into hydroxymethyl groups, or methylolmelamine is tetramethylolmelamine obtained by modifying 4 of 6 hydrogen atoms in the amino group of melamine into hydroxymethyl groups.

[0043] [Modified methylol melamine]

[0044] As described above, the modified methylolmelamine is a reaction product of methylolmelamine and an acid component.

[0045] The acid component is a component that can react with the methylol groups of methylolmelamine. Furthermore, the acid component is a component for introducing an acidic group into methylolmelamine by reacting with the methylol groups of methylolmelamine.

[0046] Examples of the acid component include carboxylic acid, phosphoric acid, and sulfurous acid.

[0047] Examples of carboxylic acids include maleic acid, succinic acid, phthalic acid, formylbenzoic acid, aminobenzoic acid, acrylic acid, methacrylic acid, and amino acids (e.g., glycine). In addition, carboxylic acids include salts and anhydrides thereof. Examples of salts of carboxylic acids include sodium maleate and sodium succinate. Examples of anhydrides of carboxylic acids include maleic anhydride, succinic anhydride, and phthalic anhydride.

[0048] Examples of phosphoric acid include phosphonobenzoic acid and aminophenylphosphonic acid. Phosphoric acid includes salts thereof. Examples of phosphoric acid salts include sodium phosphonobenzoate.

[0049] Examples of sulfurous acid include sulfobenzoic acid, formylbenzenesulfonic acid, p-aminobenzenesulfonic acid, pyrosulfous acid, and sulfurous acid. Sulfurous acid includes salts thereof. Examples of salts of sulfurous acid include sodium hydrogen sulfite, sodium sulfite, and sodium pyrosulfite. Preferred examples of sulfurous acid include sodium hydrogen sulfite, p-aminobenzenesulfonic acid, and sodium pyrosulfite. More preferred examples of sulfurous acid include sodium hydrogen sulfite.

[0050] As the acid component, sulfurous acid is preferably used.

[0051] The acid components can be used alone or in combination of two or more.

[0052] Furthermore, the modified methylolmelamine can be obtained by reacting methylolmelamine with an acid component.

[0053] In order to react methylolmelamine with the acid component, water, methylolmelamine and the acid component are mixed and heated.

[0054] The amount of the acid component added relative to 1 mol of methylolmelamine is, for example, 0.44 mol or more, preferably 0.50 mol or more, more preferably 0.60 mol or more, further preferably 0.70 mol or more, and, for example, 1.00 mol or less, preferably 0.90 mol or less, more preferably 0.80 mol or less.

[0055] As heating conditions, the heating temperature is, for example, 50° C. or higher, preferably 70° C. or higher, and for example, 100° C. or lower, preferably 90° C. or lower. The heating time is, for example, 0.5 hour or higher, preferably 1 hour or higher, and for example, 6 hours or lower.

[0056] Thus, methylolmelamine reacts with the acid component to obtain modified methylolmelamine. Specifically, one of the methylol groups in methylolmelamine can be modified into an acidic group derived from the acid component by the acid component.

[0057] That is, the modified methylol melamine has an acidic group derived from an acid component. Specifically, when the acid component is carboxylic acid, the modified methylol melamine has a carboxyl group as an acidic group. In addition, when the acid component is phosphoric acid, the modified methylol melamine has a phosphoric acid group as an acidic group. In addition, when the acid component is sulfurous acid, the modified methylol melamine has a sulfonic acid group as an acidic group. As the acidic group, preferably a sulfonic acid group can be mentioned.

[0058] More specifically, when the acid component is sodium bisulfite, methylolmelamine (the following general formula (1-3)) reacts with sodium bisulfite (the following general formula (2-1)) to obtain modified methylolmelamine (the following general formula (2-2)). The modified methylolmelamine represented by the following general formula (2-2) has a sulfonic acid group as an acidic group.

[0059] [Chemical formula 2]

[0060] Chemical formula 2

[0061]

[0062] As the modified methylol melamine, preferably, there is mentioned the modified methylol melamine represented by the above-mentioned general formula (2-2).

[0063] As described above, the modified methylolmelamine condensation resin is a polycondensate of modified methylolmelamine (modified methylolmelamine having an acidic group). The method for producing the modified methylolmelamine condensation resin will be described later.

[0064] <Polyvinyl alcohol>

[0065] When the resin is used as a raw material for a coating material for a secondary battery separator, polyvinyl alcohol is a component for imparting wettability to improve adhesion.

[0066] Examples of the polyvinyl alcohol include unmodified polyvinyl alcohol and modified polyvinyl alcohol.

[0067] As modified polyvinyl alcohol, for example, anionic group-modified polyvinyl alcohol (for example, carboxyl-modified polyvinyl alcohol, sulfonyl-modified polyvinyl alcohol) and hydrophobic group-modified polyvinyl alcohol can be mentioned. As modified polyvinyl alcohol, anionic group-modified polyvinyl alcohol can be preferably mentioned. As modified polyvinyl alcohol, carboxyl-modified polyvinyl alcohol can be more preferably mentioned.

[0068] As the polyvinyl alcohol, preferably, modified polyvinyl alcohol is used.

[0069] The saponification degree of the polyvinyl alcohol is, for example, 70 mol % or more, preferably 85 mol % or more, more preferably 90 mol % or more, further preferably 95 mol % or more, and is, for example, 100 mol % or less, preferably 99 mol % or less.

[0070] The polyvinyl alcohol can be used alone or in combination of two or more.

[0071] Alternatively, polyvinyl alcohol may be prepared as an aqueous solution of polyvinyl alcohol. In the aqueous solution of polyvinyl alcohol, the solid content concentration of polyvinyl alcohol is, for example, 5% by mass or more, and, for example, 50% by mass or less.

[0072] <Manufacturing method of resin>

[0073] The resin can be obtained by reacting a modified methylolmelamine condensation resin with polyvinyl alcohol.

[0074] Specifically, the resin can be obtained by reacting the modified methylolmelamine condensation resin with polyvinyl alcohol while producing the modified methylolmelamine condensation resin by dehydration condensation of the modified methylolmelamine. That is, such a resin is distinguished from a resin obtained by reacting vinyl alcohol with the modified methylolmelamine condensation resin obtained by dehydration condensation of the modified methylolmelamine.

[0075] Specifically, first, modified methylol melamine and polyvinyl alcohol are mixed in water, and then, while dehydration condensation of the modified methylol melamine is carried out, the modified methylol melamine condensation resin obtained by the dehydration condensation is reacted with the polyvinyl alcohol.

[0076] In the above dehydration condensation, two methylol groups in the modified methylol melamine undergo dehydration condensation, thereby obtaining a modified methylol melamine condensation resin.

[0077] In addition, in the reaction of modified methylol melamine condensation resin and polyvinyl alcohol, the methylol of modified methylol melamine condensation resin reacts with the hydroxyl of polyvinyl alcohol.The reaction of methylol and hydroxyl is, for example, recorded in Journal of Cleaner Production (Journal of Cleaner Production) 255 volumes, May 10, 2020, 120062, "Efficient removal of Congo red dye from aqueous solution by adsorbent films of polyvinyl alcohol / melamine-formaldehyde composite and bactericidal effects" in.

[0078] In this reaction, for example, an acid (for example, sulfuric acid) is added, and heating is performed in water at a pH of 5 or more and less than 8.

[0079] As heating conditions, the heating temperature is, for example, 50° C. or higher, preferably 60° C. or higher, and for example, 90° C. or lower, preferably 80° C. or lower. The heating time is, for example, 1 hour or higher, preferably 2 hours or higher, and for example, 6 hours or lower.

[0080] The mixing ratio of the modified methylol melamine relative to 100 parts by mass of the total amount of the modified methylol melamine and the polyvinyl alcohol is, for example, 70 parts by mass or more, preferably 80 parts by mass or more, more preferably 85 parts by mass or more, and, for example, 99 parts by mass or less, preferably 95 parts by mass or less.

[0081] The proportion of polyvinyl alcohol is, for example, 1 part by mass or more, preferably 5 parts by mass or more, and for example, 30 parts by mass or less, preferably 20 parts by mass or less, and more preferably 15 parts by mass or less, relative to 100 parts by mass of the total amount of modified methylol melamine and polyvinyl alcohol.

[0082] In the above manner, the modified methylolmelamine condensation resin reacts with polyvinyl alcohol to obtain a resin (aqueous solution of the resin).

[0083] It should be noted that the above-mentioned reaction from melamine to resin can be carried out continuously or batchwise.

[0084] The solid content concentration of the modified methylolmelamine condensation resin in the aqueous solution of the resin is, for example, 10 mass % or more, preferably 15 mass % or more, and for example, 40 mass % or less.

[0085] Such resins have the same acidic groups as modified methylol melamine.

[0086] It should be noted that, in the above description, methylolmelamine is reacted with an acid component to obtain modified methylolmelamine, and then the modified methylolmelamine is subjected to dehydration condensation to obtain a modified methylolmelamine condensation resin. However, depending on the amount of the acid component, sometimes all of the methylolmelamine is not reacted with the acid component and methylolmelamine remains. In such a case, three methylol groups in the methylolmelamine are condensed with two methylol groups of the modified methylolmelamine.

[0087] The resin is a reaction product of a modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol. Therefore, it has excellent heat resistance, ion permeability and storage stability.

[0088] Furthermore, the secondary battery separator coating material raw material contains the above-mentioned resin (an aqueous solution of the above-mentioned resin).

[0089] In addition, in the raw material for coating the secondary battery separator, additives such as a wetting agent, a dispersant, a hydrophilic resin, a wetting agent, a defoaming agent, and a pH adjusting agent can be mixed as needed in an appropriate ratio. That is, the raw material for coating the secondary battery separator includes additives as needed. It should be noted that the additives can be mixed during and / or after the manufacture of the above-mentioned resin.

[0090] On the other hand, since the raw material for coating the secondary battery separator includes a resin obtained using polyvinyl alcohol, it has excellent wettability. Therefore, even if the raw material for coating the secondary battery separator does not include a wetting agent, the wettability is also excellent. That is, the raw material for coating the secondary battery separator preferably includes the above-mentioned resin and does not include a wetting agent.

[0091] In the secondary battery separator coating material raw material, the solid content concentration of the resin is, for example, 10 mass % or more, preferably 15 mass % or more, and for example, 40 mass % or less.

[0092] The raw material of the coating material for secondary battery separators contains the above resin, and therefore has excellent heat resistance, ion permeability and storage stability.

[0093] <<Second Invention>>

[0094] The raw material of the coating material for secondary battery separators contains a modified methylolmelamine condensation resin having an acidic group and polyvinyl alcohol.

[0095] <Modified methylolmelamine condensation resin having an acidic group>

[0096] The modified methylolmelamine condensation resin having an acidic group is the same as the modified methylolmelamine condensation resin having an acidic group in the first invention. That is, the modified methylolmelamine condensation resin having an acidic group is a polycondensate of modified methylolmelamine. Modified methylolmelamine is a reaction product of methylolmelamine and an acid component.

[0097] Methylolmelamine is the reaction product of melamine and formaldehyde.

[0098] The amount of formaldehyde added per 1 mol of melamine is, for example, 2.4 mol or more, preferably 2.6 mol or more, more preferably 2.8 mol or more, further preferably 2.9 mol or more, and is, for example, 5.0 mol or less, preferably 4.0 mol or less, more preferably 3.3 mol or less, further preferably 3.1 mol or less.

[0099] When the amount of formaldehyde blended per 1 mol of melamine is not less than the above lower limit and not more than the above upper limit, almost all of the three amino groups in melamine can be modified into methylol groups.

[0100] In the reaction of melamine and formaldehyde, the heating temperature, heating time and pH are the same as those in the first invention.

[0101] As the methylolmelamine, preferably, there is mentioned trimethylolmelamine in which all three amino groups in melamine are modified into methylol groups.

[0102] As described above, the modified methylolmelamine is a reaction product of methylolmelamine and an acid component.

[0103] As the acid component, the acid components mentioned in the first invention can be mentioned. As the acid component, sulfurous acid is preferably mentioned.

[0104] The acid components can be used alone or in combination of two or more.

[0105] Furthermore, similarly to the first invention, the modified methylolmelamine can be obtained by reacting methylolmelamine with an acid component. Specifically, in order to react methylolmelamine with an acid component, water, methylolmelamine and an acid component are mixed and heated.

[0106] The amount of the acid component added relative to 1 mol of methylolmelamine is, for example, 0.10 mol or more, preferably 0.15 mol or more, more preferably 0.30 mol or more, further preferably 0.40 mol or more, particularly preferably 0.43 mol or more, and, for example, less than 0.70 mol, preferably 0.65 mol or less, more preferably 0.60 mol or less, further preferably 0.50 mol or less.

[0107] The heating conditions are the same as those in the first invention.

[0108] Thus, methylolmelamine reacts with the acid component to obtain modified methylolmelamine. Specifically, one of the methylol groups in methylolmelamine can be modified into an acidic group derived from the acid component by the acid component. As the acidic group, sulfonic acid is preferably used.

[0109] Furthermore, as described above, the modified methylolmelamine condensation resin having an acidic group is a polycondensate of modified methylolmelamine (modified methylolmelamine having an acidic group).

[0110] In order to polycondense the modified methylol melamine, for example, an acid (for example, sulfuric acid) is added to adjust the pH to 5 or more and less than 8, and the modified methylol melamine is heated in water.

[0111] As heating conditions, the heating temperature is, for example, 50° C. or higher, preferably 60° C. or higher, and for example, 90° C. or lower, preferably 80° C. or lower. The heating time is, for example, 1 hour or higher, preferably 2 hours or higher, and for example, 6 hours or lower.

[0112] Then, a base (eg, sodium hydroxide) is added to adjust the pH to, for example, 11 or more and 13 or less to stop the polycondensation reaction.

[0113] In the above manner, two methylol groups in the modified methylol melamine undergo dehydration condensation to obtain a modified methylol melamine condensation resin (aqueous dispersion of modified methylol melamine condensation resin).

[0114] It should be noted that the above-mentioned reaction from melamine to the modified methylolmelamine condensation resin can be carried out continuously or batchwise.

[0115] In the aqueous dispersion of the modified methylolmelamine condensation resin, the solid content concentration of the modified methylolmelamine condensation resin is, for example, 10 mass % or more, preferably 15 mass % or more, and for example, 40 mass % or less.

[0116] Such a modified methylolmelamine condensation resin has the same acidic group as that of modified methylolmelamine.

[0117] The content ratio of the modified methylol melamine condensation resin relative to the total amount of 100 parts by mass of the modified methylol melamine condensation resin and polyvinyl alcohol is, for example, 60 parts by mass or more, preferably 70 parts by mass or more, more preferably 80 parts by mass or more, and, for example, 98 parts by mass or less, preferably 90 parts by mass or less.

[0118] It should be noted that, in the above description, methylolmelamine is reacted with an acid component to obtain modified methylolmelamine, and then the modified methylolmelamine is subjected to dehydration condensation to obtain a modified methylolmelamine condensation resin. However, depending on the amount of the acid component, sometimes all of the methylolmelamine is not reacted with the acid component and methylolmelamine remains. In such a case, three methylol groups in the methylolmelamine are condensed with two methylol groups of the modified methylolmelamine.

[0119] <Polyvinyl alcohol>

[0120] Examples of the polyvinyl alcohol include the polyvinyl alcohols described in the first invention. Preferred examples of the polyvinyl alcohol include anionic group-modified polyvinyl alcohols. More preferred examples of the modified polyvinyl alcohol include carboxyl group-modified polyvinyl alcohols.

[0121] The saponification degree of the polyvinyl alcohol is the same as the saponification degree mentioned in the first invention.

[0122] The polyvinyl alcohol can be used alone or in combination of two or more.

[0123] The content ratio of the polyvinyl alcohol relative to 100 parts by mass of the modified methylol melamine condensation resin is, for example, 3 parts by mass or more, preferably 5 parts by mass or more, more preferably 6 parts by mass or more, and further preferably 10 parts by mass or more from the viewpoint of improving heat resistance. In addition, it is, for example, 60 parts by mass or less, preferably less than 50 parts by mass, more preferably 40 parts by mass or less, further preferably 30 parts by mass or less, and particularly preferably 20 parts by mass or less from the viewpoint of improving heat resistance and ion permeability.

[0124] In addition, the content ratio of polyvinyl alcohol relative to the total amount of 100 parts by mass of the modified methylol melamine condensation resin and polyvinyl alcohol is, for example, 2 parts by mass or more, preferably 10 parts by mass or more from the viewpoint of improving heat resistance, and is, for example, 40 parts by mass or less, preferably 30 parts by mass or less, and more preferably 20 parts by mass or less from the viewpoint of improving heat resistance and ion permeability.

[0125] Alternatively, polyvinyl alcohol may be prepared as an aqueous solution of polyvinyl alcohol. In the aqueous solution of polyvinyl alcohol, the solid content concentration of polyvinyl alcohol is, for example, 5% by mass or more, and, for example, 50% by mass or less.

[0126] <Preparation of raw materials for coating materials for secondary battery separators>

[0127] The secondary battery separator coating material raw material is prepared in the form of a modified methylolmelamine condensation resin having an acidic group (aqueous dispersion of modified methylolmelamine condensation resin) and polyvinyl alcohol, each of which is separately packaged and then mixed when used.

[0128] In addition, in the raw material for coating the secondary battery separator, additives such as a wetting agent, a dispersant, a hydrophilic resin, a wetting agent, a defoamer, a pH regulator, etc. can be mixed as needed in an appropriate ratio. That is, the raw material for coating the secondary battery separator includes additives as needed. It should be noted that the additive can be mixed with a modified methylol melamine condensation resin and / or polyvinyl alcohol having an acidic group.

[0129] On the other hand, since the secondary battery separator coating material raw material includes a modified methylol melamine condensation resin and polyvinyl alcohol having an acidic group, the wettability is excellent. Therefore, the secondary battery separator coating material raw material has excellent wettability even if it does not include a wetting agent. That is, the secondary battery separator coating material raw material preferably includes a modified methylol melamine condensation resin and polyvinyl alcohol having an acidic group, and does not include a wetting agent.

[0130] Since the secondary battery separator coating material raw material contains a modified methylolmelamine condensation resin having an acidic group and polyvinyl alcohol, it is excellent in heat resistance and ion permeability.

[0131] Furthermore, such a raw material of a coating material for a secondary battery separator (the first invention and the second invention) can be particularly suitably used as a raw material of a coating material for a secondary battery separator.

[0132] Hereinafter, the secondary battery separator coating material obtained by using the secondary battery separator coating material raw material will be described in detail.

[0133] 2. Coating materials for secondary battery separators

[0134] The secondary battery separator coating material includes the secondary battery separator coating material raw material and inorganic particles.

[0135] As inorganic particles, for example, oxides, nitrides, carbides, sulfates, hydroxides, and potassium titanate can be cited. As oxides, for example, aluminum oxide, silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, cerium dioxide, yttrium oxide, zinc oxide, and iron oxide can be cited. As nitrides, for example, silicon nitride, titanium nitride, and boron nitride can be cited. As carbides, for example, silicon carbide and calcium carbonate can be cited. As sulfates, for example, magnesium sulfate and aluminum sulfate can be cited. As hydroxides, for example, aluminum hydroxide and diaspore can be cited. As silicates, for example, talc, kaolinite, dickite, pearl clay, halloysite, pyrophyllite, montmorillonite, sericite, mica, magnesia chlorite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, silica sand, and glass can be cited.

[0136] As the inorganic particles, preferably, hydroxides are used, and as the inorganic particles, more preferably, diaspore is used.

[0137] The average median particle size D50 of the inorganic particles is, for example, 0.1 μm or more, preferably 0.5 μm or more, and, for example, 5 μm or less, preferably 1 μm or less.

[0138] The inorganic particles may be used alone or in combination of two or more.

[0139] The mixing ratio of the inorganic particles will be described later.

[0140] In order to produce the secondary battery separator coating material, first, inorganic particles and, if necessary, a dispersant are mixed in water to prepare an aqueous dispersion of the inorganic particles. When a dispersant is mixed, the secondary battery separator coating material contains the dispersant.

[0141] Examples of the dispersant include ammonium polycarboxylate and sodium polycarboxylate. Preferably, ammonium polycarboxylate is used as the dispersant.

[0142] The mixing ratio of the dispersant (solid content) relative to 100 parts by mass of the inorganic particles is, for example, 0.1 parts by mass or more, preferably 0.5 parts by mass or more, and, for example, 10 parts by mass or less, preferably 3 parts by mass or less.

[0143] The dispersants may be used alone or in combination of two or more.

[0144] Next, the raw material of the coating material for secondary battery separators (aqueous dispersion of the raw material of the coating material for secondary battery separators) is mixed into the aqueous dispersion of the inorganic particles and stirred.

[0145] The stirring method is not particularly limited, and examples thereof include a ball mill, a bead mill, a planetary ball mill, a vibration ball mill, a sand mill, a colloid mill, an attritor, a roll mill, a high-speed impeller dispersion, a stirrer, a disperser, a homogenizer, a high-speed impact mill, an ultrasonic dispersion, and a stirring blade.

[0146] In addition, the coating material for secondary battery separators can be mixed with the above-mentioned additives in an appropriate ratio as needed. That is, the coating material for secondary battery separators contains the above-mentioned additives as needed. In addition, the coating material for secondary battery separators preferably does not contain a wetting agent.

[0147] These additives may be used alone or in combination of two or more.

[0148] In this way, a secondary battery separator coating material can be obtained. In addition, such a secondary battery separator coating material can be obtained in the form of an aqueous dispersion dispersed in water.

[0149] The solid content concentration of the aqueous dispersion of the secondary battery separator coating material is, for example, 10 mass % or more, preferably 20 mass % or more, more preferably 30 mass % or more, and, for example, 50 mass % or less.

[0150] In addition, in the coating material (solid component) for secondary battery separators, relative to the total amount of 100 parts by mass of the raw material (solid component) for secondary battery separators and inorganic particles, the content of the raw material (solid component) for secondary battery separators is, for example, 3.0 parts by mass or more, preferably 4.2 parts by mass or more, and in addition, it is 10.0 parts by mass or less, preferably 7.0 parts by mass or less, and more preferably 6.0 parts by mass or less. In addition, relative to the total amount of 100 parts by mass of the raw material (solid component) for secondary battery separators and inorganic particles, the content of inorganic particles is 90.0 parts by mass or more, preferably 93.0 parts by mass or more, and more preferably 94.0 parts by mass or more, and in addition, for example, 97.0 parts by mass or less, and preferably 95.8 parts by mass or less.

[0151] In addition, in the coating material (solid component) for secondary battery separators, the content of the raw material (solid component) for coating material for secondary battery separators, relative to 100 parts by mass of the total amount of inorganic particles, is, for example, 3.0 parts by mass or more, preferably 4.0 parts by mass or more, more preferably 4.4 parts by mass or more, and is, for example, 10.0 parts by mass or less, preferably 7.0 parts by mass or less, more preferably 6.0 parts by mass or less, and further preferably 5.0 parts by mass or less.

[0152] The secondary battery separator coating material contains a secondary battery separator coating material raw material. Therefore, a secondary battery separator having a coating film obtained using the secondary battery separator coating material has excellent heat resistance and ion permeability.

[0153] Hereinafter, a secondary battery separator obtained by using the secondary battery separator coating material will be described in detail.

[0154] 3. Secondary battery separator

[0155] The secondary battery separator includes a porous film and a coating film of a secondary battery separator coating material disposed on at least one surface of the porous film.

[0156] [Porous membrane]

[0157] As the porous membrane, for example, a polyolefin porous membrane and an aromatic polyamide porous membrane can be cited. As the polyolefin porous membrane, for example, a polyethylene porous membrane and a polypropylene porous membrane can be cited. As the porous membrane, preferably, a polyolefin porous membrane can be cited.

[0158] The thickness of the porous film is, for example, 1 μm or more, preferably 5 μm or more, and, for example, 40 μm or less, preferably 20 μm or less.

[0159] [Coating film]

[0160] The coating film imparts heat resistance to the porous film. The coating film is formed of a coating material for a secondary battery separator.

[0161] The thickness of the coating film is, for example, 1 μm or more, and for example, 10 μm or less, and preferably 8 μm or less.

[0162] [Method for producing secondary battery separator]

[0163] The method for producing a secondary battery separator comprises the following steps: a first step of preparing a porous membrane; and a second step of applying a separator coating material on at least one surface of the porous membrane.

[0164] (1st step)

[0165] In the first step, a porous membrane is prepared.

[0166] (Second step)

[0167] In the second step, the secondary battery separator coating material is applied to at least one surface of the porous film and then dried as necessary to obtain a coating film.

[0168] In order to apply the coating material for secondary battery separator on at least one side of the porous membrane, first, a surface treatment is applied to one side of the porous membrane as needed to form a surface treatment layer on one side of the porous membrane. That is, in such a case, the secondary battery separator has a porous membrane, a surface treatment layer, and a coating film of the coating material for secondary battery separator.

[0169] As surface treatment, for example, corona discharge treatment, glow discharge treatment, plasma treatment, and ozone treatment can be cited. In this manufacturing method, from the viewpoint of improving ion permeability, it is preferred not to implement surface treatment. In other words, the secondary battery separator preferably does not have a surface treatment layer.

[0170] Moreover, as the coating method of the coating material for the secondary battery separator, there is no particular restriction, for example, a wire rod method, a gravure coating method, a small-diameter gravure coating method, a reverse roll coating method, a transfer roll coating method, a kiss coating method, a dip coating method, a micro-gravure coating method, a blade coating method, an air knife coating method, a blade coating method, a rod coating method, an extrusion coating method, a cast coating method, a die coating method, a screen printing method, and a spray coating method can be cited. As a coating method, preferably a wire rod method can be cited.

[0171] The drying temperature is, for example, 40° C. or higher, and, for example, 80° C. or lower.

[0172] In this way, a secondary battery separator is produced which includes a porous membrane and a coating film of the secondary battery separator coating material disposed on at least one surface of the porous membrane.

[0173] In the above description, the coating film of the secondary battery separator coating material is disposed on at least one surface of the porous membrane, but the coating film may be disposed on both surfaces of the porous membrane.

[0174] The secondary battery separator has a coating film of the above-mentioned secondary battery separator coating material. Therefore, the secondary battery separator has excellent heat resistance and ion permeability. Therefore, the secondary battery separator can be suitably used in the manufacture of secondary batteries.

[0175] 4. Secondary battery

[0176] The secondary battery includes a positive electrode, a negative electrode, the secondary battery separator disposed between the positive electrode and the negative electrode, and an electrolyte impregnated in the positive electrode, the negative electrode, and the secondary battery separator.

[0177] As the positive electrode, for example, a known electrode including a positive electrode current collector and a positive electrode active material stacked on the positive electrode current collector can be used.

[0178] Examples of the positive electrode current collector include conductive materials such as aluminum, titanium, stainless steel, nickel, calcined carbon, conductive polymers, and conductive glass.

[0179] The positive electrode active material is not particularly limited, and examples thereof include known positive electrode active materials such as lithium-containing transition metal oxides, lithium-containing phosphates, and lithium-containing sulfates.

[0180] These positive electrode active materials may be used alone or in combination of two or more.

[0181] As the negative electrode, for example, a known electrode including a negative electrode current collector and a negative electrode active material stacked on the negative electrode current collector can be used.

[0182] Examples of the negative electrode current collector include conductive materials such as copper and nickel.

[0183] The negative electrode active material is not particularly limited, and examples thereof include carbon active materials. Examples of the carbon active material include graphite, soft carbon, and hard carbon.

[0184] These negative electrode active materials may be used alone or in combination of two or more.

[0185] When a lithium ion battery is used as the secondary battery, the electrolyte may be, for example, a solution in which a lithium salt is dissolved in a carbonate compound such as ethylene carbonate (EC), propylene carbonate (PC), or ethyl methyl carbonate (EMC).

[0186] In order to manufacture a secondary battery, for example, a separator of the secondary battery is sandwiched between a positive electrode and a negative electrode, these are housed in a battery case (battery cell), and an electrolyte is injected into the battery case. Thus, a secondary battery can be obtained.

[0187] The secondary battery described above includes the secondary battery separator described above, and therefore has excellent heat resistance and ion permeability.

[0188] <Effects>

[0189] In the first invention, the raw material of the secondary battery separator coating material contains a resin which is a reaction product of a modified methylolmelamine condensation resin having an acidic group and polyvinyl alcohol, and therefore has excellent heat resistance and ion permeability.

[0190] Specifically, the resin is obtained by using a modified methylolmelamine condensation resin having an acidic group having excellent heat resistance. Therefore, the resin has excellent heat resistance.

[0191] In addition, since the resin is obtained using polyvinyl alcohol, it has excellent wettability, so that a coating film can be formed uniformly, thereby improving heat resistance and ion permeability.

[0192] In addition, the resin has excellent wettability, so for example, when a coating material raw material for a secondary battery separator containing the resin is applied to the surface of a porous membrane, a coating film can be formed even if the surface of the porous membrane is not subjected to surface treatment (for example, corona discharge treatment).

[0193] When the surface of the porous membrane is subjected to surface treatment, the interaction between the raw material for secondary battery separator coating and the porous membrane becomes stronger, and a part of the raw material for secondary battery separator coating may enter the pores of the porous membrane, which may reduce the ion permeability.

[0194] On the other hand, according to the raw material for coating the secondary battery separator, even if the surface of the porous membrane is not subjected to surface treatment, a coating film can be formed, thereby preventing a portion of the raw material for coating the secondary battery separator from entering the pores of the porous membrane. Therefore, the ion permeability can be further improved.

[0195] In addition, the resin is also excellent in storage stability.

[0196] Specifically, from the viewpoint of improving wettability, a method has been studied in which polyvinyl alcohol is added to a modified methylolmelamine condensation resin having an acidic group obtained by polycondensing modified methylolmelamine in advance. That is, in such a case, polyvinyl alcohol is added later.

[0197] However, in such a case, if the polyvinyl alcohol is added and then stored for a certain period of time, gelation occurs due to the interaction between the hydroxyl groups of the polyvinyl alcohol and the methylol groups of the modified methylol melamine resin.

[0198] On the other hand, the resin is obtained by reacting a modified methylolmelamine condensation resin having an acidic group obtained by dehydration condensation with polyvinyl alcohol in advance while dehydration condensation of the modified methylolmelamine is carried out. That is, in this case, polyvinyl alcohol is added in advance.

[0199] The gelation can be suppressed by reacting the modified methylol melamine condensation resin with polyvinyl alcohol in advance. The reason is not clear, but it is presumed that the hydroxyl groups of the polyvinyl alcohol are consumed in the reaction by reacting the modified methylol melamine resin with polyvinyl alcohol in advance, so that the hydroxyl groups of the polyvinyl alcohol are reduced during storage, and as a result, the storage stability can be improved.

[0200] In the second invention, the raw material of the secondary battery separator coating material contains a modified methylolmelamine condensation resin having an acidic group and polyvinyl alcohol, and therefore has excellent heat resistance and ion permeability.

[0201] Specifically, the secondary battery separator coating material raw material contains a modified methylolmelamine condensation resin having an acidic group and excellent in heat resistance. Therefore, the raw material has excellent heat resistance.

[0202] In addition, since the raw material of the coating material for the secondary battery separator contains polyvinyl alcohol, it has excellent wettability, so that a coating film can be formed uniformly, thereby improving heat resistance and ion permeability.

[0203] In addition, since the raw material of the secondary battery separator coating material has excellent wettability, a coating film can be formed even without subjecting the surface of the porous film to surface treatment (for example, corona discharge treatment).

[0204] When the surface of the porous membrane is subjected to surface treatment, the interaction between the raw material for secondary battery separator coating and the porous membrane becomes stronger, and a part of the raw material for secondary battery separator coating may enter the pores of the porous membrane, which may reduce the ion permeability.

[0205] On the other hand, according to the raw material for coating the secondary battery separator, even if the surface of the porous membrane is not subjected to surface treatment, a coating film can be formed, thereby preventing a portion of the raw material for coating the secondary battery separator from entering the pores of the porous membrane. Therefore, the ion permeability can be further improved.

[0206] The secondary battery separator coating material includes the above-mentioned secondary battery separator coating material raw material, and therefore has excellent heat resistance and ion permeability.

[0207] The secondary battery separator includes a coating film of the above-mentioned secondary battery separator coating material, and therefore has excellent heat resistance and ion permeability.

[0208] The secondary battery includes the above-mentioned secondary battery separator, and therefore has excellent heat resistance and ion permeability.

[0209] Example

[0210] The specific numerical values ​​of the mixing ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced by the upper limit value (the numerical value defined in the form of "below" or "less than") or the lower limit value (the numerical value defined in the form of "above" or "greater than") of the corresponding mixing ratio (content ratio), physical property values, parameters, etc. recorded in the above-mentioned "Specific Embodiment". In addition, in the following description, unless otherwise specified, "parts" and "%" are based on mass.

[0211] <Details of ingredients>

[0212] The trade names and abbreviations of the components used in each Example and each Comparative Example are described in detail.

[0213] AF17: Carboxyl-modified polyvinyl alcohol, saponification degree greater than 96 mol%, manufactured by JAPAN VAM&POVAL CO., LTD.

[0214] GOHSENX CKS-50: Sulfonic modified polyvinyl alcohol, saponification degree 99 mol%, manufactured by Mitsubishi Chemical Corporation

[0215] GOHSENX WO-320: Hydrophilic group-modified polyvinyl alcohol, saponification degree 98.5 mol%, manufactured by Mitsubishi Chemical Corporation

[0216] Kuraray Poval 5-98: Unmodified polyvinyl alcohol, saponification degree 98 mol% to 99 mol%, manufactured by KURARAY Co., Ltd.

[0217] Kuraray Poval 60-98: Unmodified polyvinyl alcohol, saponification degree 98 mol% to 99 mol%, manufactured by KURARAY Co., Ltd.

[0218] Kuraray Poval 44-88: Unmodified polyvinyl alcohol, saponification degree 87 mol% to 89 mol%, manufactured by KURARAY Co., Ltd.

[0219] Kuraray Poval 5-74: Unmodified polyvinyl alcohol, saponification degree 72.5-74.5 mol%, manufactured by KURARAY Co., Ltd.

[0220] Wetting agent: Acetylene surfactant, OLFINE E1010, manufactured by Nissin Chemical Industry Co., Ltd.

[0221] Ammonium polycarboxylate: dispersant, aqueous solution of ammonium polycarboxylate, trade name SN5468, manufactured by SAN NOPCO LIMITED

[0222] <<First Invention>>

[0223] <Preparation of Aqueous Solution of Polyvinyl Alcohol>

[0224] 100 parts by weight of water was added to a separable flask equipped with a stirrer, and 10 parts by weight of each polyvinyl alcohol (AF17, GOHSENX CKS-50, GOHSENX WO-320, and Kuraray Poval 5-98) was added little by little while stirring, and the temperature was raised to 95° C. and maintained for 5 hours. After confirming that the polyvinyl alcohol was completely dissolved, the mixture was cooled, and an appropriate amount of water was added to prepare a 10% aqueous solution of polyvinyl alcohol for each polyvinyl alcohol.

[0225] <Manufacturing of resin>

[0226] Production Example 1

[0227] 33.0 parts by mass of water and 114.8 parts by mass of 37% formaldehyde were placed in a four-necked flask equipped with a stirrer, a thermometer and a reflux tube, and stirred and mixed. Further, 51 parts of melamine were added under stirring. Next, the temperature was raised to 60°C, the pH was adjusted to 11.0 using a 40% aqueous sodium hydroxide solution, and then the reaction was further carried out at 67°C for 2 hours, and then cooled to 50°C. Thus, methylol melamine was obtained.

[0228] Next, 32 parts by mass of sodium bisulfite was added, the pH was adjusted to 11.5 with a 40% aqueous sodium hydroxide solution, and the reaction was carried out at 80°C for 4 hours. Thus, modified methylol melamine was obtained. Next, 150 parts by mass of an aqueous solution (10%) of AF17 and 342 parts by mass of water were added, the pH was adjusted to 6.6 with 40% sulfuric acid, the reaction was carried out at 72°C for 8 hours, and the pH was adjusted to 12.0 with a 25% aqueous sodium hydroxide solution to stop the reaction. Then, an appropriate amount of water was added. Thus, a resin (aqueous solution of resin) (solid content concentration of 16% by mass) was obtained.

[0229] Production Example 2 to Production Example 4

[0230] A resin (resin aqueous solution) (solid content concentration: 16 mass %) was obtained by the same procedure as in Production Example 1. However, the formulation of each component was changed according to Table 1. It should be noted that the values ​​described in Table 1 are parts by mass (solid content).

[0231] Comparative Manufacturing Example 1

[0232] 200.0 parts by mass of distilled water were added to a separable flask equipped with a stirrer and a reflux condenser, and the temperature was raised to 80°C after replacement with nitrogen. Then, 0.6 parts by mass of ammonium persulfate was added, and the following monomer composition was continuously added over 3 hours, and the polymerization was completed after further maintaining for 3 hours. Ammonia water was added to adjust the pH to 9.0, and then an appropriate amount of water was added to obtain an aqueous solution of a water-soluble polymer having a solid content of 16.0%.

[0233] {Monomer Composition}

[0234]

[0235] Reference Production Example 1

[0236] 692.0 parts by mass of water and 277.8 parts by mass of 37% formaldehyde were placed in a four-necked flask equipped with a stirrer, a thermometer and a reflux tube, and stirred and mixed. Further, 144.0 parts of melamine were added under stirring. The temperature was raised to 60°C, the pH was adjusted to 11.0 using a 25% aqueous sodium hydroxide solution, and then the reaction was further carried out at 75°C for 3 hours, and then cooled to 60°C. Thus, methylol melamine was obtained.

[0237] Next, 50.9 parts by mass of sodium hydrogen sulfite was added as an acid component, and the mixture was reacted at 80° C. for 2 hours. Thus, modified methylol melamine was obtained.

[0238] Next, after cooling to 40°C or less, water was added to adjust the solid content concentration to 20% by mass. The pH was further adjusted to 6.8 with 40% sulfuric acid, and condensation was performed at 70°C for 3 hours. Then, the pH was adjusted to 12.0 with a 25% sodium hydroxide aqueous solution to stop the reaction. Next, an appropriate amount of water was added to obtain a resin (aqueous solution of resin) (solid content concentration of 18% by mass).

[0239] <Manufacturing of coating material raw material for secondary battery separator, coating material for secondary battery separator, and secondary battery separator>

[0240] Example 1

[0241] (Manufacturing of raw materials for coating materials for secondary battery separators)

[0242] The resin of Production Example 1 was used as a raw material of a coating material for a secondary battery separator.

[0243] (Manufacture of coating material for secondary battery separator)

[0244] According to the formula described in Table 2, a dispersant was added to 123 parts by mass of water. Then, while stirring with a disperser (1000 rpm), 100 parts by mass of boehmite (diaspore, manufactured by Nabaltec, trade name "APYRAL AOH60", average median particle size D50: 0.9 μm) as inorganic particles was slowly added. After the addition, stirring was further performed with a homogenizer (5000 rpm). Thus, an aqueous dispersion of inorganic particles (solid content concentration of inorganic particles was 45% by mass) was obtained.

[0245] Next, the raw material of the secondary battery separator coating material is mixed into the aqueous dispersion of the inorganic particles, and water is appropriately added and stirred.

[0246] Then, the mixture was filtered using a 300-mesh filter (filtration particle size: 48 μm). Thus, a secondary battery separator coating material (dispersion of secondary battery separator coating material) was prepared. The dispersion of the secondary battery separator coating material had a solid content concentration of 40% by mass.

[0247] (Manufacturing of secondary battery separators)

[0248] [1st step]

[0249] As the porous film, a polyolefin porous film (without surface treatment (corona treatment)) was prepared.

[0250] [Step 2]

[0251] The secondary battery separator coating material (dispersion of the secondary battery separator coating material) was applied to one side of the polyolefin porous membrane using a wire rod, and then dried at 50° C. Thus, a coating film (thickness 4 μm and thickness 2 μm) of the secondary battery separator coating material was formed on one side of the polyolefin porous membrane. Thus, a secondary battery separator was manufactured.

[0252] Examples 2 to 4, Comparative Example 1 and Reference Example 1

[0253] Based on the same steps as in Example 1, a raw material for a coating material for a secondary battery separator, a coating material for a secondary battery separator, and a secondary battery separator are obtained. However, the formula of each component is changed according to Table 2. It should be noted that the values ​​recorded in Table 2 are parts by mass (solid content). In addition, in Comparative Example 1, an aqueous solution of a water-soluble polymer used in the manufacture of Comparative Example 1 as a raw material for a coating material for a secondary battery separator and E1010 are combined to manufacture a coating material for a secondary battery separator. In addition, in Reference Example 1, a resin used in the manufacture of Reference Example 1 as a raw material for a coating material for a secondary battery separator and an aqueous solution of AF (10%) are combined to manufacture a coating material for a secondary battery separator.

[0254] <Evaluation>

[0255] [Heat resistance]

[0256] The secondary battery separator of each embodiment, each comparative example and each reference example was cut into 5 cm × 5 cm and used as a test piece. The test piece was placed in an oven at 150°C for 1 hour. Before and after placement, the length of each side of the test piece was measured. Based on the following formula (1), the shrinkage rate was calculated from the length of each side before shrinkage and the length of each side after shrinkage. The results are shown in Table 2.

[0257] Shrinkage rate (%) = {average length of one side before shrinkage (cm) - average length of one side after shrinkage (cm)} / average length of one side before shrinkage (cm) × 100 (1)

[0258] [Ion permeability]

[0259] For each embodiment, each comparative example and each reference example of the secondary battery separator, the Wang Yan type air permeability smoothness tester manufactured by Asahi Seiko Co., Ltd. was used to measure the air permeability resistance in accordance with JIS-P-8117. The reduction in air permeability relative to the air permeability of the porous membrane itself is taken as Δ air permeability. Specifically, based on the following formula (2), Δ air permeability is calculated. The smaller the Δ air permeability, the better the ion permeability is evaluated. The results are shown in Table 2.

[0260] Δ air permeability = measured air permeability - 180 (air permeability of the porous membrane itself) (2)

[0261] [Storage stability]

[0262] The change in viscosity of the resin of each manufacturing example and each manufacturing reference example, and the aqueous solution of the water-soluble polymer of Comparative Example 1, when stored at 40°C for 1 month, was measured. The viscosity was measured using a VISCOMETER manufactured by Toki Sangyo Co., Ltd. at 60 rpm and 25°C. The change in viscosity was calculated based on the following formula (3). The results are shown in Table 2.

[0263] Viscosity change = (viscosity after storage at 40°C for 1 month - viscosity immediately after polymerization) / viscosity immediately after polymerization (3)

[0264] <Discussion>

[0265] It is found that Examples 1 to 4 using a resin that is a reaction product of a modified methylolmelamine condensation resin having an acidic group and polyvinyl alcohol have superior heat resistance compared to Comparative Example 1 using an acrylic water-soluble polymer.

[0266] It is found that Examples 1 to 4 in which polyvinyl alcohol was added in advance have excellent storage stability compared to Reference Example 1 in which polyvinyl alcohol was added later.

[0267] <<Second Invention>>

[0268] <Production of modified methylolmelamine condensation resin having an acidic group>

[0269] Production Example 5

[0270] 692.0 parts by mass of water and 277.8 parts by mass of 37% formaldehyde (3.43 mol) were placed in a four-necked flask equipped with a stirrer, a thermometer and a reflux tube, and stirred and mixed. Further, 144.0 parts by mass of melamine (1.14 mol) was added under stirring. The temperature was raised to 60°C, and the pH was adjusted to 11.0 using a 25% aqueous sodium hydroxide solution, and then the reaction was further carried out at 75°C for 3 hours, and then cooled to 60°C. Thus, methylol melamine was obtained.

[0271] Next, 50.9 parts by mass (0.489 mol) of sodium hydrogen sulfite was added as an acid component, and the mixture was reacted at 80° C. for 2 hours. Thus, modified methylol melamine was obtained.

[0272] Next, after cooling to below 40°C, water was added to adjust the solid content concentration to 20% by mass. The pH was further adjusted to 6.8 using 40% sulfuric acid, and after condensation was carried out at 70°C for 3 hours, the pH was adjusted to 12.0 using 25% sodium hydroxide aqueous solution to stop the reaction. Thus, a modified methylol melamine condensation resin (aqueous dispersion of modified methylol melamine condensation resin) was obtained. Next, an appropriate amount of water was added to adjust the solid content concentration of the aqueous dispersion of the modified methylol melamine condensation resin to 18% by mass.

[0273] Production Example 6

[0274] 692.0 parts by mass of water and 259.3 parts by mass of 37% formaldehyde (3.20 mol) were placed in a four-necked flask equipped with a stirrer, a thermometer and a reflux tube, and stirred and mixed. Further, 144.0 parts by mass of melamine (1.14 mol) was added under stirring. The temperature was raised to 60°C, and the pH was adjusted to 11.0 using a 25% aqueous sodium hydroxide solution, and then the reaction was further carried out at 75°C for 3 hours, and then cooled to 60°C. Thus, methylol melamine was obtained.

[0275] Next, 33.9 parts by mass (0.426 mol) of sodium hydrogen sulfite was added as an acid component, and the mixture was reacted at 80° C. for 2 hours. Thus, modified methylol melamine was obtained.

[0276] Next, after cooling to below 40°C, water was added to adjust the solid content concentration to 20% by mass. The pH was further adjusted to 6.8 using 40% sulfuric acid, and after condensation was carried out at 70°C for 3 hours, the pH was adjusted to 12.0 using 25% sodium hydroxide aqueous solution to stop the reaction. Thus, a modified methylol melamine condensation resin (aqueous dispersion of modified methylol melamine condensation resin) was obtained. Next, an appropriate amount of water was added to adjust the solid content concentration of the aqueous dispersion of the modified methylol melamine condensation resin to 18% by mass.

[0277] <Manufacturing of Acrylic Acid-Based Water-Soluble Polymer>

[0278] Production Example 7

[0279] 200.0 parts by mass of distilled water were added to a separable flask equipped with a stirrer and a reflux condenser, and the temperature was raised to 80°C after replacement with nitrogen. Then, 0.6 parts by mass of ammonium persulfate was added, and the following monomer composition was continuously added over 3 hours, and the polymerization was completed after further maintaining for 3 hours. Ammonia water was added to adjust the pH to 9.0, and then an appropriate amount of water was added to obtain an aqueous solution of a water-soluble polymer having a solid content of 20.0%.

[0280] {Monomer Composition}

[0281]

[0282] <Preparation of Polyvinyl Alcohol>

[0283] Each polyvinyl alcohol (Kuraray Poval 60-98, AF17, Kuraray Poval 44-88, Kuraray Poval 5-74) was prepared as follows. Specifically, 100 parts by weight of water was added to a separable flask equipped with a stirrer, and 10 parts by weight of polyvinyl alcohol was added little by little while stirring, and then the temperature was raised to 95° C. and maintained for 3 hours. After confirming that the polyvinyl alcohol was completely dissolved, the mixture was cooled, and an appropriate amount of water was added to prepare a 10% aqueous solution of polyvinyl alcohol.

[0284] <Manufacturing of coating material raw material for secondary battery separator, coating material for secondary battery separator, and secondary battery separator>

[0285] Examples 5 to 11 and Comparative Examples 2 to 4

[0286] (Manufacturing of raw materials for coating materials for secondary battery separators)

[0287] According to the formula described in Table 3, a modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol were prepared respectively. Thus, a raw material for coating a secondary battery separator was manufactured. In addition, in Comparative Example 4, an acrylic acid-based water-soluble polymer was used instead of the modified methylol melamine condensation resin having an acidic group. It should be noted that the values ​​described in Table 3 are values ​​of solid components.

[0288] (Manufacture of coating material for secondary battery separator)

[0289] According to the formula described in Table 3, a dispersant was added to 123 parts by mass of water. Then, while stirring with a disperser (1000 rpm), 100 parts by mass of boehmite (diaspore, manufactured by Nabaltec, trade name "APYRAL AOH60", average median particle size D50: 0.9 μm) as inorganic particles was slowly added. After the addition, stirring was further performed with a homogenizer (5000 rpm). Thus, an aqueous dispersion of inorganic particles (solid content concentration of inorganic particles was 45% by mass) was obtained.

[0290] Next, a raw material for coating a secondary battery separator (specifically, a modified methylolmelamine condensation resin (or acrylic acid-based water-soluble polymer) having an acidic group and polyvinyl alcohol prepared separately are mixed and blended) is added to the aqueous dispersion of inorganic particles, and water is appropriately added and stirred.

[0291] Then, the mixture was filtered using a 300-mesh filter (filtration particle size: 48 μm). Thus, a secondary battery separator coating material (dispersion of secondary battery separator coating material) was prepared. The dispersion of the secondary battery separator coating material had a solid content concentration of 40% by mass.

[0292] (Manufacturing of secondary battery separators)

[0293] [1st step]

[0294] As the porous film, a polyolefin porous film (without surface treatment (corona treatment)) was prepared.

[0295] [Step 2]

[0296] The secondary battery separator coating material (dispersion of the secondary battery separator coating material) was applied to one side of the polyolefin porous membrane using a wire rod, and then dried at 50° C. Thus, a coating film (thickness 4 μm) of the secondary battery separator coating material was formed on one side of the polyolefin porous membrane. Thus, a secondary battery separator was manufactured.

[0297] <Evaluation>

[0298] [Heat resistance]

[0299] Heat resistance was evaluated in the same manner as in the first invention. The results are shown in Table 3.

[0300] [Ion permeability]

[0301] The ion permeability was evaluated in the same manner as in the first invention. The results are shown in Table 3.

[0302] <Discussion>

[0303] It can be seen that Examples 5 to 11 containing modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol have excellent heat resistance and excellent ion permeability compared to Comparative Example 2 not containing polyvinyl alcohol, and Comparative Examples 3 and 4 not containing modified methylol melamine condensation resin having an acidic group.

[0304] [Table 1]

[0305] Table 1

[0306]

[0307] [Table 2]

[0308] Table 2

[0309]

[0310] [Table 3]

[0311]

[0312] It should be noted that the above invention is provided as an exemplary embodiment of the present invention, which is merely an illustration and is not to be construed as limiting. Modifications of the present invention that are obvious to those skilled in the art are also included in the appended claims.

[0313] The secondary battery separator coating material raw material, the secondary battery separator coating material, and the secondary battery separator of the present invention can be suitably used for the production of secondary batteries.

Claims

1. A coating material raw material for a secondary battery separator, comprising a resin which is a reaction product of a modified methylol melamine condensation resin having an acidic group and polyvinyl alcohol, or The modified methylol melamine condensation resin having an acidic group and the polyvinyl alcohol are included.

2. The raw material for coating the secondary battery separator according to claim 1, comprising the resin, The acidic group is a sulfonic acid group.

3. The raw material for coating the secondary battery separator according to claim 1, comprising the modified methylol melamine condensation resin having an acidic group and the polyvinyl alcohol, The content ratio of the polyvinyl alcohol is 5 parts by mass or more and less than 50 parts by mass based on 100 parts by mass of the modified methylol melamine condensation resin. 4 . A secondary battery separator coating material comprising the secondary battery separator coating material raw material according to claim 1 and inorganic particles.

5. A secondary battery separator having: a porous membrane; and A coating film of the secondary battery separator coating material according to claim 4 disposed on at least one surface of the porous film. 6 . A secondary battery comprising a positive electrode, a negative electrode, and the secondary battery separator according to claim 5 disposed between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Coat material for secondary battery separator

    JP2021103676A